2022
DOI: 10.47162/rjme.63.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on fertility and assisted reproductive technology (ART): a systematic review

Abstract: The appearance of coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been a major obstacle for the performing of current medical activities throughout the world. COVID-19 has affected humanity in many ways, thus causing a great medical, social, economic, and political instability. The aim of this study was to make an analysis of the scientific data obtained by so far to highlight the impact that COVID-19 has had on fertility and assisted reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Săndulescu, M.S et al observed that the secretion of ectopic endometrial glands into the ovarian cortex led to compression and an increase in PI or SI [52]. We also noted similar findings in this study on EO.…”
Section: Microscopic Characteristics Of a And E Local And Glandular F...supporting
confidence: 90%
“…Săndulescu, M.S et al observed that the secretion of ectopic endometrial glands into the ovarian cortex led to compression and an increase in PI or SI [52]. We also noted similar findings in this study on EO.…”
Section: Microscopic Characteristics Of a And E Local And Glandular F...supporting
confidence: 90%
“…Until now, several studies have outlined an association between SARS-CoV-2 infection and poor pregnancy outcomes [ 5 ]. For example, it was demonstrated that miscarriage, intrauterine death, fetal growth restriction, and high maternal–fetal morbidity rates were more prevalent in patients infected with this type of virus [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Published investigations, as well as previous systematic reviews and meta-analyses, have aimed to answer these questions and clarify the association between COVID-19 and fertility. Many investigators defend that sperm production can be altered, as male gonads can be vulnerable to infection [ 24 , 25 , 26 ]. This can be explained by the presence of angiotensin-converting enzyme 2 (ACE2) receptors, which are abundant in testes, seminiferous duct cells, spermatogonia, Leydig, and Sertoly cells [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%